Relationship of Personality Traits and Organizational Climate on Work Engagement Among Higher Education Personnel in the Philippines - Cainday, Marie Rosette L.; Chan, Francis Alvin O.; Bestuer, Gaspar M. (Future Science / FSH-PH Publications, 2023)
This study investigated the relationship of personality traits and organizational climate on the work engagement of the teaching and non-teaching personnel of West Visayas State University-Janiuay Campus in 2021. This descriptive research was conducted among 81 personnel of the higher education institution. The statistical tools used were frequency count, ranking, mean, and Spearman rho to analyze the data from the survey. Manchester Personality Test (MPQ) version 14.2 was utilized to measure the personality traits of the participants; the Organizational Climate Questionnaire (OCQ) was employed to determine the organizational climate; and the Utrecht Work Engagement Scale (UWES) was utilized to determine their work engagement. The dominant personality traits among teaching and non-teaching personnel are conscientiousness, rationality, and empathy. None of the personality traits have a significant relationship with work engagement. Their work engagement is high, and similarly, they perceived the organizational climate as high as well. Additionally, the dimensions of organizational climate, namely respect, planning and decision-making, innovations, relationships, commitment and morale, role clarity, communication, quality service, and training and learning, have a significant relationship with work engagement. Personnel highly engage themselves in their work given a favorable campus organizational climate, resulting in an enhanced degree of enthusiasm and dedication. Points derived from the findings were identified for consideration for inclusion in the continuous enhancement of the faculty and staff development program on campus, the human resource development plan, and policy-making pertaining to the development of human resources at the university.